Dual Role of Female Tin Panners at Pemali Village in Family Communication Relations - Ferdiana, Ferdiana; Rhonda, Mirza; Widowati, Dewi (Pancasila International Journal of Applied Social Science, 2025)
This study aims to analyze the dual roles of informal female tin miners (“pelimbang”) in Pemali Village, Bangka Regency, within the dynamics of family relationships. The main issue addressed is how women manage the burden of working in the informal mining sector while simultaneously fulfilling domestic responsibilities in a strongly patriarchal cultural context. This research employed a qualitative exploratory case study approach, using in-depth interviews, observations, and documentation involving female miners and village officials. The key findings reveal that female “pelimbang” utilize interpersonal communication strategies, such as gradual self-disclosure and open discussion, to negotiate their roles within the family. The Social Penetration Theory (SPT) explains the depth of interpersonal relationships developed through layered disclosure, while the Uncertainty Reduction Theory (URT) illustrates how these women reduce domestic tensions arising from unclear role boundaries. The study concludes that interpersonal communication plays a crucial role in maintaining family stability, despite the economic and cultural pressures these women face. These findings contribute theoretically to family communication studies and offer practical implications for policies that support the empowerment of women in the informal workforce.